Non-Observance of Gricean Maxims as a Literary Strategy in Short Fiction: A Discourse-Pragmatic Analysis of O. Henry and W. Somerset Maugham - Yokubjonova Ibodatxon Ulugbek Kizi; Mukhayyo Fayzullaeva; Satullaeva Nargiza Jalgasbaevna; Najimov Amanlik Shamshetdinovich; Sodiqova Nargiza Baxodir Qizi; Sodikova Shokhistakhon Bakhodir Qizi (Masyarakat Linguistik Indonesia Universitas Andalas, 2026)
Meaning in discourse is frequently conveyed indirectly; conversational maxims are rarely followed strictly, serving instead as tools for speakers to generate implied meaning. In literary discourse, particularly within the semantically dense genre of short fiction, the non-observance of these maxims operates not as a communicative failure but as an intentional artistic strategy to shape characterisation and narrative depth. Building on this background, this study investigates how the non-observance of Gricean conversational maxims functions as a literary strategy in selected English short stories by O. Henry and W. Somerset Maugham. Drawing on Grice’s Cooperative Principle, the analysis examines how deviations from the maxims of Quantity, Quality, Relation, and Manner generate nonconventional implicatures that extend beyond the literal content. The study focuses on four stories: The Girl and the Habit and An Unfinished Story by O. Henry, alongside The Happy Couple and The Promise by W. Somerset Maugham. Employing a qualitative discourse-pragmatic methodology, representative instances of maxim non-observance are identified and interpreted regarding their narrative context and linguistic form. The findings demonstrate that maxim non-observance functions as a vital resource for creating irony, humour, characterisation, emotional reserve, and social commentary. Comparative analysis reveals distinct stylistic applications: O. Henry frequently employs overt exaggeration, verbal play, and socially dynamic exchanges, while Maugham utilizes understatement, ambiguity, and controlled indirection to convey psychological tension and moral complexity. Ultimately, the article concludes that Gricean pragmatics offers a highly effective framework for literary analysis, elucidating how fictional dialogue constructs layered, interpretively rich meanings. Furthermore, this framework provides a practical pedagogical tool, enabling students to explicitly connect pragmatic principles to the interpretation of character motivation and narrative structure in their analytical writing.